Comprehending Knowledge, Practices, and Perceptions of Community Health Workers Regarding Adolescent Health Program: A Cross-Sectional Inquiry in Bellary District, Karnataka - P.M, Sindhu; Dmello, Mackwin Kenwood; Lobo, Prajwal Jupiter; Dsouza, Neevan (Journal of Health and Allied Sciences NU, 2023)
Introduction Community health workers are crucial in improving health and bridging gaps between communities and health care services. They are integral to various national health initiatives to prevent diseases and enhance well-being. Providing health care services to adolescents is a pivotal responsibility for auxiliary nurse midwives (ANMs) and Accredited Social Health Activist (ASHA) workers.Objectives This study aims to evaluate the community health workers' comprehension, implementation practices, and viewpoints regarding the implementation of the Rashtriya Kishor Swasthya Karyakram (RKSK) program.Methodology The research was conducted across primary health centers in Hagaribommanahalli and Huvina Hadagali taluks. A two-stage sampling technique was utilized to gather data from 404 participants, who were administered a semi-structured questionnaire. Data analysis was performed using SPSS version 20 software.Results Out of the total community health workers, 336 (83.2%) were ASHA workers, while 68 (16.8%) were ANMs. The mean age of the community health workers was 38 ± 6 years, and 79% had received training in the RKSK program. Of the respondents, 60.9% demonstrated adequate knowledge, and 79.5% correctly executed the RKSK activities. In addition, 80.5% of the participants strongly concurred with statements reflecting their perception of the RKSK program.Conclusion The study findings indicate that community health workers possess a commendable understanding of the RKSK program. Furthermore, their effective implementation practices and positive perceptions regarding the RKSK program and its activities suggest a genuine commitment to supporting the RKSK program and other health-related endeavors targeting adolescents.
Keywords: ANM; ASHA workers; knowledge; practice; perception